Functionality screening to help design effective materials for radioiodine abatement - Robshaw, Thomas J.; Turner, Joshua; Tuck, Olivia; Pyke, Caroline; Kearney, Sarah; Simoni, Marco; Sharrad, Clint A.; Walkley, Brant; Ogden, Mark D. (Frontiers in Chemistry, 2022)
This paper is part of a growing body of research work looking at the synthesis of an optimal adsorbent for the capture and containment of aqueous radioiodine from nuclear fuel reprocessing waste. 32 metalated commercial ion exchange resins were subjected to a two-tier screening assessment for their capabilities in the uptake of iodide from aqueous solutions. The first stage determined that there was appreciable iodide capacity across the adsorbent range (12-220 mg·g-1). Candidates with loading capacities above 40 mg·g-1 were progressed to the second stage of testing, which was a fractional factorial experimental approach. The different adsorbents were treated as discrete variables and concentrations of iodide, co-contaminants and protons (pH) as continuous variables. This gave rise to a range of extreme conditions, which were representative of the industrial challenges of radioiodine abatement. Results were fitted to linear regression models, both for the whole dataset (R2 = 59%) and for individual materials (R2 = 18-82%). The overall model determined that iodide concentration, nitrate concentration, pH and interactions between these factors had significant influences on the uptake. From these results, the top six materials were selected for project progression, with others discounted due to either poor uptake or noticeable iodide salt precipitation behaviour. These candidates exhibited reasonable iodide uptake in most experimental conditions (average of >20 mg·g-1 hydrated mass), comparing favourably with literature values for metallated adsorbents. Ag-loaded Purolite S914 (thiourea functionality) was the overall best-performing material, although some salt precipitation was observed in basic conditions. Matrix effects not withstanding it is recommended that metalated thiourea, bispicolylamine, and aminomethylphosphonic acid functionalised silicas warrant further exploration.